Agroindustrial waste conversion into ultramicroporous activated carbons for greenhouse gases adsorption-based processes. (June 2022) - Gomez-Delgado, Edward; Nunell, Gisel; Cukierman, Ana Lea; Bonelli, Pablo
Abstract: Activated carbons (ACs) for greenhouse gases adsorption were developed via KOH activation of waste twigs arising from processing of Ilex paraguariensis branches. The effect of KOH/carbonized twigs mass ratio (R = 1–3) and temperature (873–1073 K) was examined. The ACs showed BET areas between 1000 and 2150 m 2 g −1, total pore volumes of 0.3–1.0 cm 3 g −1, and completely microporous structures with large presence of ultramicropores (≤1.1 nm). The ACs obtained with R = 2 at 873 K attained the highest CO2 adsorption capacity (5.4 mmol g −1 ). An unprecedented correlation to estimate CO2 adsorption capacity in terms of ACs properties was developed. For the best sample, dynamic assays for CO2 and CH4 adsorption from single and binary equimolar gaseous streams were conducted at 101.32 kPa and 303 K. Regeneration showed that the ACs almost kept the initial dynamic adsorption capacity of both gases (1.4 mmol CO2 g −1 and 0.4 mmol CH4 g −1 ) after five adsorption-desorption cycles. Graphical abstract: Unlabelled Image Highlights: Waste yerba mate twigs were found suitable for activated carbons manufacture. Ultramicroporous structures led to high CO2 adsorption capacity. Process variables leading to materials with the required porosity were established. Adsorbents could be regenerated up to 5 times keeping their gas removal efficiency. Adsorbents might be used for post-combustion gas treatment and biogas purification.